La invención de los celos - Konstan, David (Pontificia Universidad Católica del Perú, 2005)
In this paper the A. proposes the idea that, in classical Greece, the concept of a feeling that exactly corresponds to Jealousy in the modern Western world. did not exist. He inquires on the meaning of the word zélotupia that is frequently translated by "jealousy", and proves that it did not have that precise meaning in the ancient Greek texts. Yet, although there was little room in archalc Greek culture for the developmenl of the idea of Jealousy in a romantic sense. in Rome's first century B.C., conditions favoured the development of such a concept, concretely in Horace's amatory poems and in the authors of erotic elegy.

En este artículo propongo la idea de que, en la Grecia clásica, no existía el concepto de un sentimiento que corresponda precisamente al de los celos en el mundo occidental moderno. Investigo el significado de la palabra zélotupia, que con frecuencia se traduce por "celos", y demuestro que no tenía exactamente este sentido en los textos griegos antiguos. Sin embargo, si había poco espacio en la cultura de la Grecia arcaica para el desarrollo de la idea de celos en el sentido romántico, en Roma en el siglo primero a.C. las condiciones favorecían la formación de tal concepto, concretamente en la poesía amatoria de Horacio y los autores de la elegía erótica.
The Invention of Jealousy
Keywords: Jealousy; Greece; Rome; Poetry.; Celos; Grecia; Roma; Poesía.; https://purl.org/pe-repo/ocde/ford#6.03.01